Tekanan Investor dan Tanggung Jawab Profesi: Studi Etika Akuntan pada Kasus eFishery - Nisrina Zulfa Khairani; Estika Triwidya Fajar; Salsabila Tuhfatul Aulia; Cindy Apriliany Laura; Yanuar Ramadhan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study examines violations of accounting professional ethics in the case of financial statement manipulation at eFishery, which reflects a dilemma between investor pressure and accountants’ professional responsibility. The pressure to demonstrate rapid growth and high valuation prompted management to engage in manipulative practices involving accountants in the preparation of financial reports that deviated from the principles of integrity and objectivity. The purpose of this study is to analyze the forms of ethical violations against the five fundamental principles of the Code of Ethics for Professional Accountants, integrity, objectivity, professional competence and due care, confidentiality, and professional behavior. The research employs a qualitative descriptive approach through 26 literature reviews of academic journals, reports, and accounting profession regulations. The findings indicate that ethical violations in the eFishery case are systemic, influenced by structural pressure and an organizational culture that normalizes opportunistic behavior. Analysis based on deontological, utilitarian, and agency theories confirms that such manipulative actions cannot be morally justified, as they cause long-term harm to public trust and the reputation of the accounting profession. This study emphasizes the importance of strengthening ethical awareness, moral education within the profession, and implementing internal control mechanisms and whistleblowing systems within startups as preventive measures to uphold the integrity of the accountant profession.